Impact of Brain Injury on Processing of Emotional Prosodies in Neonates - Sun, Guoyu; Xie, Hui; Liu, Yanan; Chen, Yu; Hou, Xinlin; Zhang, Dandan (Frontiers in Pediatrics, 2019)
Being able to appropriately process different emotional prosodies is an important cognitive ability normally present at birth. In this study, we used event-related potential (ERP) to assess whether brain injury impacts the ability to process different emotional prosodies (happy, fear and neutral) in neonates; whether the ERP measure has potential value for the evaluation of neurodevelopmental outcome in later childhood. A total of 42 full-term neonates were recruited from the neonatology department of Peking University First Hospital from June 2014 to January 2015. They were assigned to the brain injury group (n = 20) or control group (n = 22) according to their clinical manifestations, physical examinations, cranial images and routine EEG outcomes. Using an oddball paradigm, ERP data were recorded while subjects listened to happy (20%, deviation stimulus), fearful (20%, deviation stimulus) and neutral (80%, standard stimulus) prosodies to evaluate the potential prognostic value of ERP indexes for neurodevelopment at 30 months of age. Results showed that while the mismatch responses (MMRs) at the frontal lobe were larger for fearful than happy prosody in control neonates, this difference was not observed in neonates with brain injuries. This finding suggests that perinatal brain injury may influence the cognitive ability to process different emotional prosodies in neonatal brain; this deficit could be reflected by decreased MMR amplitudes in response to fearful prosody. Moreover, the decreased MMRs at the frontal lobe was associated with impaired neurodevelopment at 30 months old.